Severe Hyponatremia Is Often Drug Induced: 10‐Year Results of a Prospective Pharmacovigilance Program. Issue 6 (10th September 2019) - Ramírez, Elena; Rodríguez, Amelia; Queiruga, Javier; García, Irene; Díaz, Lucía; Martínez, Lucía; Muñoz, Raúl; Muñoz, Mario; Tong, Hoi Y.; Martínez, José Carlos; Borobia, Alberto M.; Carcas, Antonio J.; et al.
Abstract : We conducted a prospective evaluation of drug‐induced severe hyponatremia  (adverse drug reaction (ADR)) through the Prospective Pharmacovigilance Program from Laboratory Signals at Hospital over a period of 10 years. Cases of serum sodium (Na(s)) < 116 mM were recorded from July 2007 to June 2017 (first period). Also cases of Na(s) 116–122 mM were recorded from July 2012 to June 2017 (second period). Drugs were the primary cause of severe hyponatremia. The incidence rate of Na(s) < 116 mM by drugs was increased threefold over the decade. Compared with other causes of hyponatremia, patients with adverse drug reaction–serum sodium (ADR‐Na(s)) in the first period were older (79 years (interquartile range (IQR) 68.6–89 vs. 65 years (IQR 48–81); P  < 0.001) and were more often women (70.8% vs. 48.9% men, P  < 0.001); in the second period were also older (79 years (IQR 65.3–89) vs. 63 years (IQR 46–80.6); P  <   0.001) and were more often women (70% vs. 53%, P  =   0.002), and ADR‐Na(s) occurred more often in summer. The most frequent therapeutic groups of culprit drugs were the cardiovascular system and nervous system. The 65.3% in the first period and 71.2% in the second period of the ADR‐Na(s) cases responded to hydration and had been diagnosed with hypovolemic hyponatremia.